2020
DOI: 10.3390/ijerph17218187
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study Using a Machine Learning Suicide Risk Prediction Model Based on Open-Ended Interview Language in Adolescent Therapy Sessions

Abstract: Background: As adolescent suicide rates continue to rise, innovation in risk identification is warranted. Machine learning can identify suicidal individuals based on their language samples. This feasibility pilot was conducted to explore this technology’s use in adolescent therapy sessions and assess machine learning model performance. Method: Natural language processing machine learning models to identify level of suicide risk using a smartphone app were tested in outpatient therapy sessions. Data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The NLP/ML pipeline used in this study followed similar techniques used by Pestian et al, focused on the term frequency of n-grams (contiguous sequence of n number of words) and SVMs (21,22,(40)(41)(42). The Porter Stemmer algorithm was applied to participant language to normalize morphologically related terms (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NLP/ML pipeline used in this study followed similar techniques used by Pestian et al, focused on the term frequency of n-grams (contiguous sequence of n number of words) and SVMs (21,22,(40)(41)(42). The Porter Stemmer algorithm was applied to participant language to normalize morphologically related terms (43).…”
Section: Discussionmentioning
confidence: 99%
“…During SVM tuning, hyperparameters considered include: the regularization parameter (C), the kernel (radial basis function and linear kernels), the kernel coefficient (gamma, if applicable), and the class weight. Additional details on NLP/ML methods may be found in previous work (42). We have evaluated the performance of Logistic Regression and XGBoost models in previous work and found comparable performance across models (42), and therefore decided to continue with the SVM used previously (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide spectrum of AI tools was used in these 13 studies. A combination of NLP and ML was used in four studies [11][12][13][14]. ML as the exclusive AI technique was used in four studies [15][16][17][18], artificial neural network (ANN) was used in three studies [19][20][21], and NLP in two studies [9,22].…”
Section: Ai Toolsmentioning
confidence: 99%
“…Thus, although suicide prediction appears to be a difficult pursuit [16], suicide risk identification is a necessary step to determine the level of suicide-specific care that may be warranted. Cohen and colleagues [17] conducted a feasibility investigation of whether machine learning techniques with natural language processing of adolescent discussions with their therapists may improve suicide risk assessment practices. The investigation demonstrated that this practice focused on augmenting standardized clinical risk assessment efforts may provide important information for assessing risk of STBs and thus the cueing of suicide-specific care practices.…”
mentioning
confidence: 99%